CAUSES AND FACTORS OF ECONOMIC INEQUALITY IN THE CONTEXT OF LABOR MARKET TRANSFORMATION IN UZBEKISTAN (Scientific electronic journal "Labor Economics and Human Capital", 2026)
This article examines the impact of globalization, digitalization, and technological advancements on economic inequality in the context of labor market transformation. It analyzes the mechanisms and factors shaping economic inequality in Uzbekistan’s labor market. Digitalization and technological changes increase the demand for highly skilled workers, while low-skilled workers lose competitiveness, and the high share of informal employment combined with insufficient social protection exacerbates income disparities. Based on empirical and international data, trends in the labor markets of Uzbekistan, CIS countries, and OECD states are compared. The study results provide scientifically grounded recommendations to reduce economic inequality through the reduction of the informal sector, enhancement of skills and digital literacy, expansion of social protection systems, and reduction of regional disparities.
Keywords: Labor market, economic inequality, transformation, informal employment, digitalization, qualifications and skills, labor force, social protection, employment policy, regional disparities.